Characterizing Cracking and Permanent Deformation; an Attempt for Predicting the End of the Structural Pavement Life. (2017) - Pramesti, Florentina P.; Molenaar, A.A.A.; van de Ven, M.F.C.
Abstract: Durable, therefore sustainable, road needs to attain specific characteristics, among others, resistance to permanent deformation and cracking. Determining the development of both characteristics are important to be able to predict pavement life and performance. In this research, permanent deformation occurring in three pavement sections was measured by a transverse profilograph. The pavement sections were simple two layer structures consisting of a gravel asphalt concrete (GAC) layer on a sand subgrade. The length and the width of the section are 16 m and 4 m respectively. These three sections were tested by means of Lintrack, an Accelerated Pavement Test (APT) which allows large number of realistic wheel load applied in a limited period of time. The results of this measurements shows the development of permanent deformation, which is defined as 'rut depth', as function of the number of load repetitions. Using relation exists between the radius of curvature of a deflection profile and the tensile strain at the bottom of a slab, the creep/permanent strain as a result of permanent deformation was calculated. This paper is carried out to determine relations between the rut depth and the radius of curvature and between the rut depth and the creep/permanent strain. Also, cracking development was observed upon these three pavement section. The result shows that there is a rather good correlation between rut depth and permanent/creep strain which is independent of the layer thickness.